Application of the Method for Analysis and Problem Solving (MASP) in inventory control of a steelworks - Chaves, Roger Elias; Feroni, Rita de Cassia (Brazilian Journal of Production Engineering, 2025)
The steel industry is a fundamental sector for the economy, being responsible for the production of steel, which is an essential raw material for several industries. Efficient inventory management in this segment is crucial to ensure competitiveness and reduce operating costs. This study aimed to analyze the quantity of raw material in stock in the production sector of a steel mill, seeking to understand the causes of excess product stock and propose solutions based on the MASP tool. This article portrayed the causes of the reduction in inventory turnover, gathering information directly from the company and, subsequently, mapping actions to determine the cause of the problem. To this end, integrated with MASP, tools such as the ABC curve, Ishikawa Diagram and 5W1H were used. The main cause of the problem was the excess stock of coal on ships due to a maintenance stop at a berth in the port terminal. The implementation of the action plan involved measures such as postponing deliveries and managing the raw material yard. The study reinforces the importance of MASP as an effective tool for inventory management, promoting continuous improvement and optimization of the company’s logistics processes.